All Detectable High-Molecular-Mass Penicillin-Binding Proteins Are Modified in a High-Level β-Lactam-Resistant Clinical Isolate of Streptococcus mitis - Amoroso, Ana Maria (2001)
All detectable high-molecular-mass penicillin-binding proteins (HMM PBPs) are altered in a clinical isolate of Streptococcus mitis for which the b-lactam MICs are increased from those previously reported in our region (cefotaxime MIC, 64 mg/ml). These proteins were hardly detected at concentrations that saturate all PBPs in clinical isolates and showed, after densitometric analysis, 50-fold-lower radiotracer binding. Resistance was related to mosaic structure in all HMM PBP-coding genes, where critical region replacement was complemented not only by substitutions already reported for the closely related Streptococcus pneumoniae but also by other specific replacements that are presumably close to the active-site serine. Mosaic structure was also presumed in a pbp1a-sensitive strain used for comparison, confirming that these structures do not unambiguously imply, by themselves, detectable critical changes in the kinetic properties of these proteins.